2017
DOI: 10.1515/ijm-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Microfoundations of dynamic capabilities for innovation: a review and research agenda

Abstract: This paper provides a conceptual overview of the microfoundations of dynamic capabilities for innovation. A critical evaluation of dynamic capabilities theory highlights its contested nature and significant limitations in its application. Notably, there is little understanding of the mechanisms determining the origin and evolution of dynamic capabilities, while the role of employees has been neglected. In an effort to address this deficiency, the paper draws on literature from HRM and innovation management to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 75 publications
3
52
0
10
Order By: Relevance
“…Breznik et Hisrich (2014) envisagent les capacités dynamiques comme des composantes clés de la capacité d'innovation (Boly, 2014 ;Forsman, 2011). Elles facilitent l'adaptation au changement (Hill et Rothaermel, 2003) et influencent la capacité de la firme à maintenir, à améliorer, à reconfigurer ses actifs et à en créer de nouveaux (Ambrosini et Bowman, 2009 ;Fallon-Byrne et Harney, 2017 ;Teece, 2007). Les capacités dynamiques sont donc des dimensions déterminantes de la capacité d'innovation.…”
Section: Les Capacités Dynamiques Au Coeur De La Capacité D'innovationunclassified
See 3 more Smart Citations
“…Breznik et Hisrich (2014) envisagent les capacités dynamiques comme des composantes clés de la capacité d'innovation (Boly, 2014 ;Forsman, 2011). Elles facilitent l'adaptation au changement (Hill et Rothaermel, 2003) et influencent la capacité de la firme à maintenir, à améliorer, à reconfigurer ses actifs et à en créer de nouveaux (Ambrosini et Bowman, 2009 ;Fallon-Byrne et Harney, 2017 ;Teece, 2007). Les capacités dynamiques sont donc des dimensions déterminantes de la capacité d'innovation.…”
Section: Les Capacités Dynamiques Au Coeur De La Capacité D'innovationunclassified
“…En ce sens, les capacités d'adaptation et d'évolution sont importantes, notamment pour les PME qui évoluent dans un environnement particulièrement incertain (Felin, Foss, Heimeriks et Madsen, 2012 ;O'Connor, 2008). Cependant, les recherches antérieures montrent des difficultés pour définir et caractériser les micro-fondations de ces CD (Baretto, 2010 ;Dixon, Meyer et Day, 2014 ;Fallon-Byrne et Harney, 2017 ;Wang, Senaratne et Rafiq, 2015) tout comme elles ne proposent pas de consensus sur la nature précise du lien entre capacité d'innovation et CD (Breznik et Hisrich, 2014). Il n'existe pas dans la littérature de définition ou de caractérisation des micro-fondations des CD qui influencent la capacité d'innovation des PME (Fallon-Byrne et Harney, 2017 ;Teece, 2007 ;Wu, 2010).…”
Section: Les Capacités Dynamiques Au Coeur De La Capacité D'innovationunclassified
See 2 more Smart Citations
“…The importance of dynamic capability in relation to innovation has been noticed and examined since the introduction of dynamic capability theory [37,44,45]. However, the antecedents of dynamic capability remain largely unexplored [46]. A few studies have found that learning is the major mechanism underlying the creation and development of dynamic capability [44,47]; cognitive competences of top management are critical to dynamic capability [48,49]; social capital is necessary for the seizing, integration, and releasing of resources by firms [50]; and the leadership style influences corporate learning, which in turn influences the dynamic capability [51].…”
Section: Dynamic Capabilitymentioning
confidence: 99%